Membangun Kepemimpinan Entrepreneurial Sebagai Upaya Keberhasilan Memimpin Building Entrepreneurial Leadership as an Effort to Lead Success - Yulian Anouw (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
Building Entrepreneurial Leadership as a Foundation for Successful Leadership Efforts is needed in a leader, but it cannot be denied that Building Entrepreneurial Leadership as a Foundation for Youth Success which is highly expected is often neglected by many Christian leaders. God has given gifts to every youth, the gifts that each local government has are different, these gifts are apostles and prophets, preachers of the Gospel as well as pastors and leaders of organizational people, all of these are to equip the saints (Ephesians 4:11) means that leaders are soul architects to shape the character of subordinate participants. Subordinates are very quick to imitate others, especially those they admire, so every Christian leader must plan how to make them into the people he will mold. Implementation of Building Entrepreneurial.